Please Factorise this question..
![2x ^{3} + 5x {}^{2} - 11x + 4 2x ^{3} + 5x {}^{2} - 11x + 4](https://tex.z-dn.net/?f=2x+%5E%7B3%7D+%2B+5x+%7B%7D%5E%7B2%7D+-+11x+%2B+4)
Answers
Answered by
3
Answer:
(x - 1)(2x - 1)(x + 4)
Step-by-step explanation:
Given : p(x) = 2x³ + 5x² - 11x + 4
By hit and trial method.
Putting x = 1, we get
→ p(1) = 2(1)³ + 5(1)² - 11(1) + 4
= 2 + 5 - 11 + 4
= 11 - 11
= 0
Hence, (x - 1) is a factor of above polynomial.
Dividing the above polynomial by (x - 1), we get
(For division, see the attachment.)
→ 2x² + 7x - 4
Using Middle Term Factorisation
→ 2x² + 8x - x - 4
→ 2x(x + 4) - 1(x + 4)
→ (2x - 1)(x + 4)
Hence,
2x³ + 5x² - 11x + 4 = (x - 1)(2x - 1)(x + 4)
Attachments:
![](https://hi-static.z-dn.net/files/d10/4cc11652b935b0ea954e0030d615411d.jpg)
Similar questions